Smart Supplier Selection Menggunakan Metode TOPSIS pada Sistem Pendukung Keputusan Berbasis Web - Fatkhurrochman, Fatkhurrochman; Nela Septi Wulandari; Tri Yusnanto; Kapti; Muhammad Abdul Muin; Wahyu Priyoatmoko; Fatimah Nur Arifah (STMIK BINA PATRIA, 2026)
Supplier selection is an important process in supporting a company's operational activities. CV Semangat Baru still conducts supplier evaluations manually, causing the decision-making process to become less effective, time-consuming, and prone to errors. This study aims to design and develop a web-based decision support system to assist in selecting the best supplier using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The research method used is software engineering with the Software Development Life Cycle (SDLC) Waterfall development model. The system was developed using PHP programming language and MySQL database. The criteria used in the supplier selection process include product quality, delivery timeliness, price, delivery distance, and supplier reputation. The TOPSIS method was applied to rank suppliers based on the highest preference value. The results showed that the system was able to support the supplier evaluation process in a more systematic, objective, and efficient manner. Based on Black Box testing, all system functions operated properly with a success rate of 100%, while user evaluation results obtained a feasibility score of 91.3%, categorized as highly feasible. Therefore, the web-based decision support system using the TOPSIS method can assist CV Semangat Baru in determining the best supplier more quickly and accurately.